Феномен мовчання героя у творчості Іво Андрича - Рудяков, П. (Слово і Час, 2008)
У статті досліджується феномен мовчання героя у творчості Іво Андрича. На матеріалі кількох оповідань
і роману “Проклятий двір” розглянуто специфіку мовчання як особливого стану свідомості персонажа,
окреслено місце героя, який мовчить, у структурі оповіді, його взаємозв’язок із героєм-оповідачем,
героєм-переповідачем та героєм-слухачем. This article deals with the phenomenon of silence in the works by Ivo Andric. The author of this essay analyses
some of Andric’s short stories as well as his novel “The Damned Yard” in order to define the specific character of
silence as a special state of character’s consciousness. He also outlines the place of the “silent” characters within the narrative structure of the text and the way such a character correlates with the narrator, the reteller and the
listener of the story. В статье исследуется феномен молчания героя
в творчестве Иво Андрича. На материале нескольких
рассказов и романа “Проклятый двор” показано
специфику молчания как особенного состояния
сознания персонажа, определено место героя
молчащего в структуре повествования, его
взаимосвязь с героем-рассказчиком, героемпересказчиком,
героем слушающим.